POLA WAHYU MEMANDU ILMU DALAM PENANAMAN AKIDAH AKHLAK GENERASI MILENIAL - Miftahul Fikri (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2019)
Morals suffer from a crisis at the level of application, because the concept of understanding Morals is quite easy to understand. Applying the creed in accordance with the teachings of religion and morals exemplified by the Prophet was not easy to apply, requiring certain patterns to be more easily applied. The purpose of writing this article is to provide a picture of the pattern in the cultivation of moral principles based on revelation to guide knowledge for millennial generation. The writing method uses the Sufi approach to the upright pyramid. Findings related to morality are weak belief in God with forms of fellowship in God that are not felt, and findings related to morality there are cases of immorality and many other cases that illustrate the corruption. This article discusses the pattern of planting a moral faith based on revelation to be applied in daily life rather than only at the level of science. Millennials who are now entering the heyday are in the spotlight. The pattern that is used refers to the concept of the magnets of sustenance that is at an applicative and practical level. The pattern used by positivating thoughts, positiveness of feelings and positivation of motivation. Planting positive thoughts by training yourself to always think positively, positively respond to the facts that occur, keep away the suuzan, substituting negative words for positive. Planting positive feelings by training yourself to be grateful for all circumstances, accepting the reality, believing that the calamity that comes must be accompanied by great pleasure, multiply reading the Koran, and focus on worship of God. Positive inculcation of motivation by practicing refrains from actions that fall into the zones of lust that have negative energy, and trains oneself to do actions that fall into the zone of piety that has positive energy.